The Impact of HDI, Minimum Wages, Investment and GRDP on Poverty in East Java in 2019 - Qurrata, Vika Annisa; Ramadhani, Nadiah (KnE Social Sciences, 2021)
Poverty is a serious problem in East Java. Many policies are carried out to reduce poverty such as intensified economic growth, improvement in the quality of human resources, increasing UMK annually and promoting investment. This research examined the influence of the Human Development Index (HDI), Small Medium Enterprises (SMEs), investment, and GRDP on poverty in East Java in 2019. Cross-sectional data of 38 regency cities in East Java were analyzed using linear regression. The results showed that HDI had a significant effect on poverty in East Java. Keywords: poverty, HDI, investment, minimum wage, GRDP